Review Of The Causes Of Inpatient Dispute Claim At RSUD Prof. Dr. Margono Soekarjo Purwokerto - Yupi Baraning Putri; Eliyah (Public Health and Safety International Journal, 2024)
Dispute claims are caused by 3 things, namely administration, coding, and medical. At RSUD Prof. Dr. Margono Soekarjo Purwokerto in 2020 there were inpatient claim dispute files of 3.6% and in 2021 there were inpatient claim dispute files of 7.4%. The purpose of this study was to identify the causes of inpatient claim dispute at RSUD Prof. Dr. Margono Soekarjo Purwokerto. This type of research is quantitative with a cross-sectional approach. The research sample was 50 inpatient claim dispute files for the period January-July 2022. Data processing techniques using collecting, editing, entry, cleaning, tabulating, presenting data. The results showed that the percentage of coding disputes related to the suitability of diagnosis and procedure codes using ICD 10 and ICD 9 CM was 52%, related to diagnoses or procedures that should be coded in combination, but coded separately by 18%, related to diagnoses or procedures that should not be entered by 18%, and related to the determination of the main diagnosis by 14%. Medical disputes related to the appropriateness of medical actions amountedto 32%, related to the appropriateness of medical treatment with diagnosis codes amounted to 2%, and related to the appropriateness of supporting examination results with diagnosis codes amounted to 2%. Administrative disputes related to the appropriateness of the results of supporting examinations / actions amounted to 4%, related to the SEP was 2% inappropriate, and 2% there was no SEP KLL.